Temperature-sensitive sarcomeric protein post-translational modifications revealed by top-down proteomics - Cai,W; Hite,ZL; Lyu,B; Wu,Z; Lin,Z; Gregorich,ZR; Messer,AE; McIlwain,SJ; Marston,SB; Kohmoto,T; Ge,Y (Journal of Molecular and Cellular Cardiology, 2018)
Despite advancements in symptom management for heart failure (HF), this devastating clinical syndrome remains the leading cause of death in the developed world. Studies using animal models have greatly advanced our understanding of the molecular mechanisms underlying HF; however, differences in cardiac physiology and the manifestation of HF between animals, particularly rodents, and humans necessitates the direct interrogation of human heart tissue samples. Nevertheless, an ever-present concern when examining human heart tissue samples is the potential for artefactual changes related to temperature changes during tissue shipment or sample processing. Herein, we examined the effects of temperature on the post-translational modifications (PTMs) of sarcomeric proteins, the proteins responsible for muscle contraction, under conditions mimicking those that might occur during tissue shipment or sample processing. Using a powerful top-down proteomics method, we found that sarcomeric protein PTMs were differentially affected by temperature. Specifically, cardiac troponin I and enigma homolog isoform 2 showed robust increases in phosphorylation when tissue was incubated at either 4°C or 22°C. The observed increase is likely due to increased cyclic AMP levels and activation of protein kinase A in the tissue. On the contrary, cardiac troponin T and myosin regulatory light chain phosphorylation decreased when tissue was incubated at 4°C or 22°C. Furthermore, significant protein degradation was also observed after incubation at 4°C or 22°C. Overall, these results indicate that temperature exerts various effects on sarcomeric protein PTMs and careful tissue handling is critical for studies involving human heart samples. Moreover, these findings highlight the power of top-down proteomics for examining the integrity of cardiac tissue samples.